Initial Development of the Intersectionality Pedagogy Scale - Thompson, Jenae D.; Frazier, Walter L. (Journal of Teaching and Learning, 2025)
In this study, an instrument was developed to measure an instructor’s value and incorporation of intersectionality theory in the classroom. Through a Delphi study, a list of items was devised, and then a pilot study was conducted to collect responses from 161 participants. The result is the development of the Intersectionality Pedagogy Scale, a 23-item scale with a single factor that measures intersectionality pedagogy. The implications for this study will be discussed, along with recommendations for further research.